The Function And Important Of The Narrator In Film : Narrative - Taş Öz, Perihan (Marmara Üniversitesi İletişim Fakültesi, 2012)
The relationship between audience and film narrative, as well as methods used in film narrative are changing according to the increasing possibilities born in film narration, in parallel with the developments in motion picture. Hence, the function and status of the narrator as a key element in film narrative takes on importance. The narrator, not only gives information on the world of the film to the audience, but also directs them. The narrative is formed according to the point of view of the narrator and the audience views and understands the film in accordance with this point of view.
Keywords: Narrative; Filmic Narrative; Narrator